Lewis acid-promoted direct synthesis of isoxazole derivatives - Qiu, Dengxu; Jiang, Chenhui; Gao, Pan; Yuan, Yu (Beilstein Journal of Organic Chemistry, 2023)
Isoxazole derivatives were synthesized via a one-pot method utilizing 2-methylquinoline derivatives as template substrates, sodium nitrite as a nitrogen-oxygen source, and solely using aluminum trichloride as the additive. This approach circumvents the need for costly or highly toxic transition metals and presents a novel pathway for the synthesis of isoxazole derivatives.
Keywords: aluminum trichloride; Lewis acid; isoxazole derivatives; sodium nitrite; transition metals